Selecting first-line immunotherapy in advanced melanoma: Current evidence on efficacy across diverse patient populations - Sophia Kreft; Tommaso Bosetti; Rebecca Lee; Paul Lorigan (EJC Skin Cancer)
Immunotherapy has dramatically changed the outcome for patients with advanced melanoma, with significant improvements in overall survival and potential cure for some. The recent approval of nivolumab in combination with relatlimab (nivolumab-relatlimab) added a third immunotherapy option for first-line treatment for advanced melanoma. Nivolumab-relatlimab has shown greater efficacy compared to single-agent nivolumab and has fewer unacceptable side effects compared to the combination of ipilimumab and nivolumab (ipilimumab-nivolumab). However, the lack of both long-term follow-up data and direct comparison with ipilimumab-nivolumab raises uncertainty about where to position nivolumab-relatlimab in clinical practice. Since most patients who respond to combination ipilimumab-nivolumab also respond to nivolumab-relatlimab, and many to single-agent anti-programmed death-1 (PD-1) monotherapy, the challenge is to identify the subgroup of patients who need ipilimumab-nivolumab and would not achieve similar benefits from less toxic alternatives. This review discusses the available data on efficacy of the three approved first-line immunotherapies (single-agent anti-PD-1, nivolumab-relatlimab or ipilimumab-nivolumab) and their value in distinct population groups to help guide clinical decisions.